Determinants of Accounting Information System Performance (Micro, Small, and Medium Enterprises in Bogor Regency, West Java) - Daito, Apollo (DINASTI RESEARCH, 2024)
The global competition becomes the greatest challenge being faced by the organizations. The decision making process determines the survival of the organizations. One of the important resources that play a role in decision making is information. Most of the information needed is the organization's accounting information. Micro, Small, and Medium Enterprises (SMEs) have started implementing accounting or bookkeeping for the specific purpose of taxation , credit, capital, developing a business, and so on . However, the application of accounting information systems (bookkeeping or recording) is not necessarily effective and efficient. Accounting information system performance is influenced by certain factors . This study aims to obtain empirical evidence of the influence of organizational culture, organizational commitment, staff competence, and change management to the accounting information system performance. To test the empirical facts, logic necessary arrangement with the Background theory: Karl Marx (1818-1883), Max Weber (1864-1920), Grand Theory: Georg Simmel (1838-1918), Ralf Dahrendorf (1929-2009), Lewis A Coser (1913-2003), Middle Range Theory: Jensen & Meckling (1976), Application Theory: Schein (1992), Hofstede (1991), Iceberg Theory, Wood et al (2001), Luthans (1992), Spencer (1993), Potts & LaMarsh (2004), Huczynski & Buchanan (1991). The research unit is 101 respondents in SMEs in West Jakarta. Methods of analysis tools using path analysis or a combination of correlation and regression to determine the effect of partial and simultaneous. The results of the study after the test of validity, reliability, and the transformation of ordinal data to interval shows the results: organizational culture, organizational commitment, staff competence, change management have significant and positive effect on the performance of accounting information systems partially or simultaneously adjusted R square value of 0.672 or 67.2 % and the rest are other factors outside of the model of 0.328 or 32.8 %. Results of this study have consistency with the entire framework, literature review, and previous research. The suggestion for the study: a) necessary for the development of advanced research outside the model, (b) for SME policies need to consider the development of organizational culture, organizational commitment, staff competence, and change management to improve the performance of accounting information systems.